Lingual choristoma - Saniasiaya , Jeyasakthy; Mohamad , Irfan; Abdul Ghani, Melati; Hoo, Hui Ling (Ministry of Health, Brunei Darussalam, 2015)
Osseous choristoma is a rare, benign tumour of the oral cavity. It is composed of normal lamellar bone occurring at an abnormal site. The aetiology and pathogenesis of this lesion remains debatable. Most are asymptomatic and usually present with mass effect. We report a case of a young lady who presented with globus pharyngeus secondary to a lingual choristoma.